An ancient anatomic variation: bilateral elongated styloid process of cranium - Ozdemir, M. Bulent; Okunak, Mehmet; Koseler, Aylin; Simsek, Celal; Atalay, Erol; Yonguc, Goksin Nilufer (Italian Journal of Anatomy and Embryology, 2013)
The elongated stylohyoid process presents with considerable anatomic variability. We report here on an ancient cranium with bilateral elongated styloid process, 3.3 cm on the right side and 5.1 cm on the left side, found during the examination of excavated bones of 2000 years ago (first half of 1st century AD) from the old Greek-Roman city-of Leodikya in Turkey. We determined the gender as female, from the examination of the skeleton (especially skull and pelvic bones). No other variation was observed. On the basis of embryology, the reason for this variation may be partial ossification of the second pharyngeal arch cartilage in the region which commonly becomes the stylohyoid ligament. Although elongation of the styloid process is common, it is important to report this ancient variation, in order to help to compare the bone variations between ancient and modern humans and the contribution of genetic and environmental determinants.